Magnetic recovery reveals sequential extraction bias and supports mass-conservative assessment of lanthanum-based sediment phosphorus inactivation - Zhe Wang; Liling Wang; Chengyan Bao; Enyang Liu; Xinnuo Liu; Zezhen Pan; Feijian Mao; Xingxing Wang; Jiake Li; Deyi Wu; Qiang Xie; Zimeng Wang (Water Research, 2026)

Characterization and modification of chickpea husk dietary fibers: Potential applications in gummy candy and emulsion-based food products - Xiangyu Liu; Yifan Zhang; Liang Wang; Minwei Zhang; Fen Li; Huiling Yan; Kaiwen Wu; Feng Zhang; Qiao Zhang; Jun Liu; Chunlan Zhang; Liling Wang; et al. (Food Hydrocolloids, 2026)

Engineered aptamer-confined hydrogel for label-free detection of heavy-metal ions with enhanced interference tolerance - Long Bai; Xiuxiu Wu; Lei Huang; Haohao Chen; Jinsong Yu; Ziqing Ye; Min Yuan; Hui Cao; Liling Hao; Fengqin Yin; Tai Ye; Fei Xu (Food Chemistry, 2026)

Preparation of K2CO3-activated biochar from peanut shell and Chlorella for enhanced carbamazepine adsorption: Performance, mechanism, and reusability - Zhenzhen Li; Jiayu Wu; Ting Cheng; Liling Zhou; Yujia Yang (Journal of Environmental Management, 2026)

Engineering Agriophyllum squarrosum starch-butyric acid complexes with functional properties via ionic liquids-ultrasonication synergy - Shaopan Cao; Yuxin Yang; Yongye Wu; Yang Hu; Jie Zhang; Shilong Cheng; Si Wu; Yang Liu; Liling Zhang; Ling Jiang (Food Research International, 2026)

Ecological effects and governance implications of transboundary river migration between China and Vietnam: A multidimensional analysis of the past, present and future - Liling Liao; Wenzhu Zhang; Zheng Cui; Bin Wu; Shengquan Lu; Shuangmi Xie (Process Safety and Environmental Protection, 2026)

Antimony exposure promotes cardiac fibrosis via lactate-mediated cardiomyocyte-fibroblast crosstalk: A novel Sirt1-glycolysis axis - Xin Li; Zhenzhen Dai; Xiaoyong Ren; Hao Zhao; Lirong Chan; Ruotong Wu; Xinyi Xiao; Qiao Liu; Liling Su (Journal of Environmental Sciences, 2026)

Coactive adaptation to combined drought and UV-B stress in highland barley (qingke) through hormonal and nutrient crosstalk - Noman Shoaib; Liling Liu; Nishbah Mughal; Xiaoyun Bai; Fakhar Zaman; Yan Pan; Juan Zhang; Junjie Pan; Xiaogang Wu; Xiaoming Sun; Lin Zhang; Kaiwen Pan (Plant and Soil, 2026)

Removal of PFAS and 1,2,4-TCB from firefighting-contaminated sites by iron-modified biochar microspheres loaded with microbes - Binglu Teng; Zhenhua Zhao; Jiangxuan Wu; Liling Xia; Yuan Jiang; Yipin Geng (Journal of Cleaner Production, 2026)

Study on PFAS removal by different forms of iron-modified biochar: Adsorption effects and catalytic activity - Binglu Teng; Zhenhua Zhao; Jiangxuan Wu; Liling Xia; Yuanchi Wang; Jiayuan Cheng; Wenqing Zhang; Hailong Wang (Journal of Environmental Chemical Engineering, 2025)

Study on the effect of alginate coated Ca-Fe bimetallic composite biochar microspheres on the removal of short-chain PFAS - Binglu Teng; Zhenhua Zhao; Jiangxuan Wu; Liling Xia; Yuanchi Wang; Hailong Wang; Olive M. Yemele; Muhammad Adnan (Environmental Research, 2025)

A novel marine biomineralization bacterium Exiguobacterium sp. 9–2: Inducing calcium carbonate precipitation with ferric ion-mediated facilitation - Tingting Zhu; Liling Xu; Zhengli Wu; Lijing Yang; Zhenlun Song (Journal of Environmental Chemical Engineering, 2025)

Contact-dependent antagonism is mediated by a T7SSb toxin effector–immunity protein pair via ADP-ribosylation - Hongxin Guan; Huan Wu; Mengrou Gan; Jing Zhang; Jiajun Wang; Siyao Liu; Shuyue Chen; Yindi Jiao; Fan Li; Shiqing Huang; Sihuang Lin; Hongwei Chen; et al. (Science Bulletin, 2025)

Analysis of the molecular karyotype of Kengyilia grandiglumis on the Qinghai-Tibet Plateau via sequential FISH and GISH - Ruijuan Liu; Liling Jiang; Yijun Zhong; Yue Wu; Demei Liu; Wenjie Chen (Genetic Resources and Crop Evolution, 2025)

Mediation role of gut microbiota in the association between ambient fine particulate matter components and cardiovascular disease: Evidence from a China cohort - Shaokun Yang; Rui Yu; Fen Yang; Jiawei Li; Lele Wang; Gonghua Wu; Liling Chen; Tingting Yang; Zhuoma Duoji; Yanjiao Wang; Xufang Gao; Yuanyuan Liu (Environmental Research, 2025)

A simplified in-situ extraction method for pyrethroid pesticides from complex food matrix through pore-switching response based on rationally designed Zr-MOFs with anti-interference performance - Lei Huang; Qianwen Yang; Yujie Yang; Tai Ye; Hui Cao; Liling Hao; Xiuxiu Wu; Fei Xu (Chemical Engineering Journal, 2025)

Fluorescent nanozyme for the dual-mode detection of tetracycline: Aggregation-induced luminescence and boosting peroxidase-like activity - Tai Ye; Long Bai; Jinsong Yu; Weiyan Shi; Min Yuan; Juncheng Wang; Hui Cao; Liling Hao; Xiuxiu Wu; Fengqin Yin; Fei Xu (Food Control, 2025)

Microbiologically influenced corrosion inhibition of carbon steel by a novel bacterium, Photobacterium sp., in simulated marine environment - Tingting Zhu; Liling Xu; Lijing Yang; Pingping Zhao; Xinglong Zhu; Zhengli Wu; Zhenlun Song (Environmental Research, 2025)

Bi2O2Se nanosheets coated with rosmarinic acid for colon-targeted treatment of inflammatory bowel disease - Jiahu Yao; Yang Yang; Hu Zhao; Chuanming Wang; Liang Jin; Tengyun Long; Wei Huang; Xiang Zhan; Xin Li; Xin Chen; Jinhu Xie; Bin Wu; et al. (Chemical Engineering Journal, 2025)

Progress on the removal of PFAS contamination in water by different forms of iron-modified biochar - Binglu Teng; Zhenhua Zhao; Liling Xia; Jiangxuan Wu; Hailong Wang (Chemosphere, 2024)

Synergistic reduction of air pollutants and carbon dioxide emissions in Shanxi Province, China from 2013 to 2020 - LiLing Wu; Shida Sun; Gaige Zhang; Zimu Jia; Yuyun Liu; Chenxi Xu; Mengjie Guo; Luyao Zhang; Cilan Cai; Runcao Zhang; Jialin Zheng; Wenjie He; et al. (Science of The Total Environment, 2024)

Polystyrene microplastics trigger testosterone decline via GPX1 - Jiayuan Qu; Liling Wu; Li Mou; Changjiang Liu (Science of The Total Environment, 2024)

Optimization of Cr(VI) ion-imprinted polymer with imidazole derivatives as functional monomers and its binding mechanism - Mengyuan Huang; Yuanyuan Yang; Hui Cao; Min Yuan; Tai Ye; Liling Hao; Jinsong Yu; Fengqin Yin; Fei Xu; Xiuxiu Wu (Journal of Environmental Chemical Engineering, 2024)

Correlation between urinary rare earth elements and liver function in a Zhuang population aged 35–74 years in Nanning - Xingxi Luo; Liling Wei; Shun Liu; Kaili Wu; Dongping Huang; Suyang Xiao; Erna Guo; Lei Lei; Xiaoqiang Qiu; Xiaoyun Zeng (Journal of Trace Elements in Medicine and Biology, 2024)

Associations between metal(loid) exposure with overweight and obesity and abdominal obesity in the general population: A cross-sectional study in China - Tianran Shen; Liling Zhong; Guiyuan Ji; Baolan Chen; Mengfan Liao; Lvrong Li; Huiming Huang; Jiajie Li; Yuan Wei; Shan Wu; Zihui Chen; Wenjun Ma; et al. (Chemosphere, 2024)

Targeting anticancer immunity in oral cancer: Drugs, products, and nanoparticles - Liling Qin; Jianan Wu (Environmental Research, 2023)

Adverse effects of triclosan exposure on health and potential molecular mechanisms - Xuhui Chen; Li Mou; Jiayuan Qu; Liling Wu; Changjiang Liu (Science of The Total Environment, 2023)

The ecological response and distribution characteristics of microorganisms and polycyclic aromatic hydrocarbons in a retired coal gas plant post-thermal remediation site - Zhenhua Zhao; Barry Mody Oury; Liling Xia; Zhirui Qin; Xiangyu Pan; Jichan Qian; Fangzhou Luo; Yong Wu; Luqi Liu; Wei Wang (Science of The Total Environment, 2023)

Afforestation can lower microbial diversity and functionality in deep soil layers in a semiarid region - Weibo Kong; Xiaorong Wei; Yonghong Wu; Mingan Shao; Qian Zhang; Michael J. Sadowsky; Satoshi Ishii; Peter B. Reich; Gehong Wei; Shuo Jiao; Liping Qiu; Liling Liu (Global Change Biology, 2022)
Afforestation is an effective approach to rehabilitate degraded ecosystems, but often depletes deep soil moisture. Presently, it is not known how an afforestation‐induced decrease in moisture affects soil microbial community and functionality, hindering our ability to understand the sustainability of the rehabilitated ecosystems. To address this issue, we examined the impacts of 20 years of afforestation on soil bacterial community, co‐occurrence pattern, and functionalities along vertical profile (0–500 cm depth) in a semiarid region of China's Loess Plateau. We showed that the effects of afforestation with a deep‐rooted legume tree on cropland were greater in deep than that of in top layers, resulting in decreased bacterial beta diversity, more responsive bacterial taxa and functional groups, increased homogeneous selection, and decreased network robustness in deep soils (120–500 cm). Organic carbon and nitrogen decomposition rates and multifunctionality also significantly decreased by afforestation, and microbial carbon limitation significantly increased in deep soils. Moreover, changes in microbial community and functionality in deep layer was largely related to changes in soil moisture. Such negative impacts on deep soils should be fully considered for assessing afforestation's eco‐environment effects and for the sustainability of ecosystems because deep soils have important influence on forest ecosystems in semiarid and arid climates.

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Liangyi Gao extends lifespan and exerts an antiaging effect in Caenorhabditis elegans by modulating DAF-16/FOXO - Liling Zeng; Chen Sun; Zhong Pei; Tianchan Yun; Shaoyi Fan; Simei Long; Tengteng Wu; Ziwen Chen; Zhimin Yang; Fuping Xu (Biogerontology, 2019)

Aquaporin 5 is degraded by autophagy in diabetic submandibular gland - Yan Huang; Xijin Shi; Qianying Mao; Yan Zhang; Xin Cong; Xueming Zhang; Zhejing Zhang; Liling Wu; Ruolan Xiang; Guangyan Yu (Science China Life Sciences, 2018)

Interactive effects of global change factors on soil respiration and its components: a meta‐analysis - Lingyan Zhou; Xuhui Zhou; Junjiong Shao; Yuanyuan Nie; Yanghui He; Liling Jiang; Zhuoting Wu; Shahla Hosseini Bai (Global Change Biology, 2016)
As the second largest carbon (C) flux between the atmosphere and terrestrial ecosystems, soil respiration (Rs) plays vital roles in regulating atmospheric CO 2 concentration ([CO 2 ]) and climatic dynamics in the earth system. Although numerous manipulative studies and a few meta‐analyses have been conducted to determine the responses of Rs and its two components [i.e., autotrophic (Ra) and heterotrophic (Rh) respiration] to single global change factors, the interactive effects of the multiple factors are still unclear. In this study, we performed a meta‐analysis of 150 multiple‐factor (≥2) studies to examine the main and interactive effects of global change factors on Rs and its two components. Our results showed that elevated [ CO 2 ] (E), nitrogen addition (N), irrigation (I), and warming (W) induced significant increases in Rs by 28.6%, 8.8%, 9.7%, and 7.1%, respectively. The combined effects of the multiple factors, EN , EW , DE , IE , IN , IW , IEW , and DEW , were also significantly positive on Rs to a greater extent than those of the single‐factor ones. For all the individual studies, the additive interactions were predominant on Rs (90.6%) and its components (≈70.0%) relative to synergistic and antagonistic ones. However, the different combinations of global change factors (e.g., EN , NW , EW , IW ) indicated that the three types of interactions were all important, with two combinations for synergistic effects, two for antagonistic, and five for additive when at least eight independent experiments were considered. In addition, the interactions of elevated [ CO 2 ] and warming had opposite effects on Ra and Rh, suggesting that different processes may influence their responses to the multifactor interactions. Our study highlights the crucial importance of the interactive effects among the multiple factors on Rs and its components, which could inform regional and global models to assess the climate–biosphere feedbacks and improve predictions of the future states of the ecological and climate systems.